Empirical evaluation of interest barrier effects - Daniel Dreßler; Uwe Scheuering (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper empirically estimates the effects of a new thin-capitalization rule on the financing behavior of German corporations employing a fixed effects difference-in-difference approach. We compare treatment and control groups separated by a hypothetical application of the new rule in three years before its introduction. Our analysis does not provide empirical evidence for a pure interest barrier effect. This indicates that the few affected firms were either unable to reduce their leverage or used exceptions. The observable trend towards less debt might stem from a general preference for lower debt ratios after the crisis or from the tax rate cut, which was introduced simultaneously.
Keywords: F23; H25; H32; 330; Capital Structure; Corporate Taxation; Interest Barrier; Empirical Analysis; Firm-Level Data